2004
DOI: 10.1084/jem.20041061
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriModulates the T Helper Cell 1/T Helper Cell 2 Balance through Phase-variable Interaction between Lipopolysaccharide and DC-SIGN

Abstract: The human gastric pathogen Helicobacter pylori spontaneously switches lipopolysaccharide (LPS) Lewis (Le) antigens on and off (phase-variable expression), but the biological significance of this is unclear. Here, we report that Le+ H. pylori variants are able to bind to the C-type lectin DC-SIGN and present on gastric dendritic cells (DCs), and demonstrate that this interaction blocks T helper cell (Th)1 development. In contrast, Le− variants escape binding to DCs and induce a strong Th1 cell response. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
267
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(270 citation statements)
references
References 57 publications
1
267
1
1
Order By: Relevance
“…Varying the overall frequency of Lewis antigen expressors within a H. pylori population would be one mechanism whereby H. pylori modulates the inf lammatory response within the stomach (25,26). We envision that, in a persistent infection of a human stomach, a number of variants of a strain exist, and each isolate is more or less unique with respect to surface molecules, such as LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Varying the overall frequency of Lewis antigen expressors within a H. pylori population would be one mechanism whereby H. pylori modulates the inf lammatory response within the stomach (25,26). We envision that, in a persistent infection of a human stomach, a number of variants of a strain exist, and each isolate is more or less unique with respect to surface molecules, such as LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Signal transduction upon ligand binding to DC-SIGN has not yet been proven, although the presence of an intracellular immunoreceptor tyrosine-based activation motif (ITAM) similar to dectin-1 suggests that DC-SIGN could be a signaling receptor [30]. Additionally, interactions of DC-SIGN with certain pathogens may have direct consequences for Th1/Th2 polarization [31]. Interestingly, blocking of the interaction between DC and T cells with an anti-DC-SIGN antibody influences allostimulatory properties in T cells [1].…”
Section: Blocking the Interaction Of L1-vlp With Dc-sign Inhibits Vlpmentioning
confidence: 99%
“…Bergman et al 48 demonstrated that Le-positive H. pylori strains were able to interact with the C-type lectin DC-SIGN on the surface of gastric dendritic cells. This interaction blocks maturation of T-helper 1 cells and leads to general immune suppression and reduced production of pro-inflammatory cytokines.…”
Section: Peptidoglycanmentioning
confidence: 99%
“…Contrarily, Le-negative strains do not show specific binding to dendritic cells through DC-SIGN, promoting maturation of T-helper 1 cells and thereby inducing a stronger immune response. 48 The marked diversity of Lewis antigen expression makes it difficult to define their role in infection and disease progression. However, evidence abounds to suggest that helical shape of H. pylori.…”
Section: Peptidoglycanmentioning
confidence: 99%
See 1 more Smart Citation